Peer audience effects on children's vocal masculinity and femininity. (3rd January 2022) - Cartei, Valentina; Reby, David; Garnham, Alan; Oakhill, Jane; Banerjee, Robin
Abstract : Existing evidence suggests that children from around the age of 8 years strategically alter their public image in accordance with known values and preferences of peers, through the self-descriptive information they convey. However, an important but neglected aspect of this 'self-presentation' is the medium through which such information is communicated: the voice itself. The present study explored peer audience effects on children's vocal productions. Fifty-six children (26 females, aged 8–10 years) were presented with vignettes where a fictional child, matched to the participant's age and sex, is trying to make friends with a group of same-sex peers with stereotypically masculine or feminine interests (rugby and ballet, respectively). Participants were asked to impersonate the child in that situation and, as the child, to read out loud masculine, feminine and gender-neutral self-descriptive statements to these hypothetical audiences. They also had to decide which of those self-descriptive statements would be most helpful for making friends. In line with previous research, boys and girls preferentially selected masculine or feminine self-descriptive statements depending on the audience interests. Crucially, acoustic analyses of fundamental frequency and formant frequency spacing revealed that children also spontaneously altered their vocal productions: they feminized their voices when speaking to members of the ballet club, while they masculinized their voices when speaking to members of the rugby club. Both sexes also feminized their voices when uttering feminine sentences, compared to when uttering masculine and gender-neutral sentences. Implications for the hitherto neglected role of acoustic qualities of children's vocal behaviour in peer interactions are discussed. This article is part of the theme issue 'Voice modulation: from origin and mechanism to social impact (Part II)'.